Comparative evaluation of antimicrobial efficacy of calcium hydroxide, triple antibiotic paste, and 2% chlorhexidine combined with 0.5% cetrimide against Enterococcus faecalis biofilm-infected dentin model: An In vitro study - Shreya; Gaurav Jain; Srinkhala; Priyansha Singh; Kishan Agarwal (Wolters Kluwer Medknow Publications, 2021)
Background: Enterococcus faecalis is the most common and important microorganism found in infected root canals associated with persistent periapical periodontitis and failing endodontically treated tooth. Intracanal medicaments used after chemomechanical preparation of an infected root canal play a vital in eradication of this microorganism and pave the way for long-term success of endodontic therapy. Hence, the present in vitro study was conducted to assess the antimicrobial efficacy of calcium hydroxide (Ca(OH)2), triple antibiotic paste (metronidazole 400 mg + minocycline 100 mg + ciprofloxacin 500 mg), and 2% chlorhexidine (CHX) combined with 0.5% cetrimide on eradication of E. faecalis biofilm. Materials and Methods: Eighty dentin specimens were taken and infected extraorally with E. faecalis to induce microbial colonization. The specimens were then divided into four groups of twenty each based on medicaments used and further subdivided into two subgroups based on assessment of live cells done either immediately after the elimination of the medicament or after 24-h incubation in brain-heart infusion (BHI) medium: Group I specimens were treated with Ca(OH)2, Group II with triple antibiotic paste, Group III with 2% CHX combined with 0.5% cetrimide, and Group IV with saline (control) for 7 days at 37°C. Assessment of live cells was done using confocal microscope. Results: 2% CHX combined with 0.5% cetrimide (Group III) and triple antibiotic paste (Group II) showed a statistically significant result with high antimicrobial efficacy and lower percentage of live cells as compared to Ca(OH)2 (Group I). The mean percentage of live cells in Group I immediately after elimination of medicaments was 64.7%, in Group II was 1.52%, in Group III was 1.49%, and in Group IV was 83.4%. After 24 h of incubation in BHI medium, 2% CHX combined with 0.5% cetrimide (Group III) showed a statistically significant (p < 0.05) result of 1.27% mean live cells as compared to 84.2% in Ca(OH)2 (Group I), 1.82% in triple antibiotic paste (Group II), and 94.2% in saline (Group IV control). Conclusion: 2% CHX combined with 0.5% cetrimide exhibited maximum antimicrobial efficacy with least number of mean live cells followed by triple antibiotic paste as compared to Ca(OH)2. Based on these findings, 2% CHX combined with 0.5% cetrimide was most effective in eradicating E. faecalis from the extraorally infected dentine biofilm.